Non-parenchymal cells: key targets for modulating chronic liver diseases - Yang, Tongwang; Gu, Zhiyun; Feng, Juan; Shan, Juanjuan; Qian, Cheng; Zhuang, Na (Frontiers in Immunology, 2025)
Non-neoplastic chronic liver diseases (CLDs), including alcoholic liver disease, metabolic-associated fatty liver disease, viral hepatitis, fibrosis, and cirrhosis, pose a global health challenge due to progressive fibro-inflammatory remodeling. Emerging evidence highlights the pivotal roles of non-parenchymal cells (NPCs)—liver sinusoidal endothelial cells (LSECs), hepatic stellate cells (HSCs), Kupffer cells (KCs), and innate immune lymphocytes such as natural killer (NK) and natural killer T (NKT) cells—in driving disease progression. Chronic liver injury triggers LSEC capillarization, HSC transdifferentiation into collagen-producing myofibroblasts, and KC polarization toward pro-inflammatory phenotypes, collectively exacerbating extracellular matrix deposition and immune dysregulation. Dysfunctional NK/NKT cells play dual roles in antiviral defense and fibrosis amplification through excessive cytokine production. This review summarizes recent advances in understanding NPC-driven mechanisms underlying chronic liver injury and fibrosis, with a focus on LSEC dysfunction, HSC activation, and inflammation mediated by KCs and NK/NKT cells. Furthermore, we delve into emerging therapeutic strategies aimed at targeting NPC-specific pathways, including mechanotransduction modulation in LSECs, metabolic reprogramming of HSCs, and regulation of KC polarization. These approaches provide valuable insights into halting CLD progression and advancing the development of innovative antifibrotic therapies.